+0

# Need help

0
281
3

how i can get the "r"

Guest May 31, 2017

#1
+7340
+3

$$\frac{E}{e}=\frac{R+r}{R-r}$$

Multiply both sides of the equation by  (R - r)  .

$$(R-r)\,*\,\frac{E}{e}=R+r$$

Distribute the   $$\frac{E}{e}$$  .

$$R*\frac{E}{e}\,-\,r*\frac{E}{e}=R+r$$

Add   $$r*\frac{E}{e}$$   to both sides of the equation.

$$R*\frac{E}{e}=R+r+r*\frac{E}{e}$$

Subtract R from both sides of the equation.

$$R*\frac{E}{e}-R=r+r*\frac{E}{e}$$

Factor out an   r   on the right side.

$$R*\frac{E}{e}-R=r(1+\frac{E}{e})$$

Divide both sides of the equation by   $$(1+\frac{E}{e})$$  .

$$\frac{R*\frac{E}{e}-R}{1+\frac{E}{e}}=r$$

hectictar  May 31, 2017
#1
+7340
+3

$$\frac{E}{e}=\frac{R+r}{R-r}$$

Multiply both sides of the equation by  (R - r)  .

$$(R-r)\,*\,\frac{E}{e}=R+r$$

Distribute the   $$\frac{E}{e}$$  .

$$R*\frac{E}{e}\,-\,r*\frac{E}{e}=R+r$$

Add   $$r*\frac{E}{e}$$   to both sides of the equation.

$$R*\frac{E}{e}=R+r+r*\frac{E}{e}$$

Subtract R from both sides of the equation.

$$R*\frac{E}{e}-R=r+r*\frac{E}{e}$$

Factor out an   r   on the right side.

$$R*\frac{E}{e}-R=r(1+\frac{E}{e})$$

Divide both sides of the equation by   $$(1+\frac{E}{e})$$  .

$$\frac{R*\frac{E}{e}-R}{1+\frac{E}{e}}=r$$

hectictar  May 31, 2017
#2
+94181
0

Good work Hectictar :)

There is no way I could read this question, it was just too small.

Melody  Jun 1, 2017
#3
0

Solve for r:
E/e = (r + R)/(R - r)

E/e = (r + R)/(R - r) is equivalent to (r + R)/(R - r) = E/e:
(r + R)/(R - r) = E/e

Cross multiply:
e (r + R) = E (R - r)

Expand out terms of the left hand side:
e r + e R = E (R - r)

Expand out terms of the right hand side:
e r + e R = E R - E r

Subtract e R - E r from both sides:
r (E + e) = E R - e R

Divide both sides by E + e:
Answer: | r = (E R - e R)/(E + e)=R[E - e] / [E + e]

Guest Jun 1, 2017